2020
DOI: 10.1007/s12649-019-00924-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extraction and Characterisation of Lipids, Proteins, and Chitin from Black Soldier Fly (Hermetia illucens) Larvae, Prepupae, and Pupae

Abstract: Over the past years, several insect species have gained increased attention as feedstock for food, feed, and industrial applications. One such species is Hermetia illucens, whose larvae can convert low-value organic waste into valuable fat-and protein-rich biomass. Previous research on extracting their lipids, proteins, and chitin has repeatedly focused on one life stage, while in practice different life stages coexist in the same rearing batch. In this study, the feasibility of the sequential extraction of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 50 publications
9
75
4
2
Order By: Relevance
“…The most abundant insect unsaturated fatty acids (UFAs) are oleic acid (C18:1 cis 9) and linoleic acid (C18:2 cis 9,12) (Paul et al, 2017;Rumpold and Schlüter, 2013;Sosa and Fogliano, 2017). However, as we mentioned previously, FA content and composition strongly depend on insect species and stage of development (Paul et al 2017;Smets et al, 2020). Only a few insect lipids are solid at room temperature and are thus called insect fats.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant insect unsaturated fatty acids (UFAs) are oleic acid (C18:1 cis 9) and linoleic acid (C18:2 cis 9,12) (Paul et al, 2017;Rumpold and Schlüter, 2013;Sosa and Fogliano, 2017). However, as we mentioned previously, FA content and composition strongly depend on insect species and stage of development (Paul et al 2017;Smets et al, 2020). Only a few insect lipids are solid at room temperature and are thus called insect fats.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
“…However, the nutrients profile of the H. illucens varied during different stages of the life cycle (it increased from 4.8% of DM on the first day of larval age to 28.4% of DM on the 14 th day of age) and was also influenced by the rearing substrate (Liu et al, 2017, Smets et al, 2020.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
“…This polysaccharide is the major component of the insect's cuticle and creates a strong skeleton together with minerals and proteins. The exoskeleton of insects is different from crustaceans by having more amino acids strongly bound to the chitin [39,40] and the degree of chitin deacetylation is dependent on the insect life stage [41]. Inclusion of chito-oligosaccharide (derivates from chitosan) in a corn-soybean meal diet has been shown to reduce the incidences and score of diarrhea in piglets weaned at 16 days of age [42], and in piglets weaned at 21 days of age and challenged with Escherichia coli [43].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that pH had a significant effect on lipid separation [34], which is vital in wet mode fractionation. Lipids, proteins and chitin were sequentially extracted from the larvae, prepupae and pupae of BSFs with a standard procedure, which proves the feasibility of obtaining valuable biomolecules from BSFs of different life stages reared on low-value organic waste streams with different composition [35]. Systematic approaches for the extraction and fractionation of proteins, lipids, and chitin from BSF prepupa were proposed [30].…”
Section: Fractionationmentioning
confidence: 95%
“…The protein solubility curve for BSF at different life stages as a function of pH was elucidated and the maximum protein solubility for all samples appeared in the basic range of 10 to 12. The isoelectric pH for precipitation of solubilized protein in alkaline medium was identified within the pH range of pH 4-4.5 [35]. The possible explanation for the limited overall yield of protein from BSFL when compared to other insects like Tenebrio molitor and Acheta domesticus could be the presence of insoluble proteins in the matrix.…”
Section: Protein Extractionmentioning
confidence: 96%